Kajian Kepemimpinan Gereja dalam Menjalankan Fungsi Gereja di Metaverse - Ekoliesanto, Yesaya Bangun; Utama, Asaf Kharisma Putra (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
Human civilization has progressed so rapidly that it is in the era of the revolution industry 4.0 and society 5.0 which is often called as the era of digital technology. A functioning church in this era must be able to adapt to face the phenomena of the times, including the birth of the metaverse church. This research uses a combination of quantitative and qualitative methods with literature studies to complement the results of research on how leadership can carry out the functions of the church in the metaverse. Church leadership must be open to new possibilities and able to adapt to changes occurring within and to the church. The metaverse church is a form of church as a result of the church's adaptation to changing times which is complementary and integrated with the church in the real world as the main organization where both work together to achieve the goal of carrying out their functions.